Design, synthesis, and insecticidal and fungicidal activities of quaternary ammonium salt derivatives of a triazolyphenyl isoxazoline insecticide. Issue 5 (19th February 2022) - Huang, Shi‐sheng; Zhu, Bin‐bing; Wang, Kai‐hua; Yu, Mo; Wang, Zi‐wen; Li, Yongqiang; Liu, Yu‐xiu; Zhang, Peng‐li; Li, Shou‐jun; Li, Ya‐ling; Liu, Ai‐ling; Wang, Qing‐min
Abstract: BACKGROUND: Insect pests seriously decrease the yield and quality of agricultural crops. Resistance to commonly used insecticides is increasingly undermining their effectiveness, and therefore the development of agents with novel modes of action is desirable. Isoxazolines are a new class of insecticides that act on γ‐aminobutyric acid (GABA) gated chloride channels. In this work, we used the highly active 4‐triazolyphenyl isoxazoline DP ‐9 as a parent structure to design and synthesize a series of quaternary ammonium salt (QAS) derivatives, and we systematically evaluated their insecticidal and antifungal activities. RESULTS: Many of the synthesized QASs exhibit insecticidal activities equivalent to or higher than that of DP ‐9 . In particular, compounds I ‐31 (93%, 0.00005 mg/L) and I ‐34 (80%, 0.00001 mg/L) showed insecticidal activities against diamondback moth larvae that were 2–10 times higher than those of fluralaner (70%, 0.0001 mg/L) and DP ‐9 (80%, 0.0001 mg/L), in addition to showing excellent activities against oriental armyworm, fall armyworm, cotton bollworm, corn borer, and mosquito larvae. Furthermore, all of the synthesized compounds also showed broad‐spectrum fungicidal activities. CONCLUSION: The insecticidal activities of QAS derivatives of DP ‐9 were the same as or better than the activity of DP ‐9 . Compounds I ‐31 and I ‐34 showed better insecticidal activities against diamondback moth larvae than fluralaner and DP ‐9, and thus are promising new candidates for insecticide research. Abstract : A series of quaternary ammonium salt derivatives were designed, synthesized, and systematically evaluated insecticidal and fungicidal activities. Compounds I ‐31 and I ‐34 with excellent insecticidal activities emerged as new candidates. © 2022 Society of Chemical Industry.